2020
DOI: 10.1080/02619768.2020.1803268
|View full text |Cite
|
Sign up to set email alerts
|

Teachers as researchers and the issue of practicality

Abstract: Practitioner research should be sufficiently trustworthy and useful. We argue, however, that although criteria of trustworthiness are rather well developed, criteria of usefulness are not. As a result, the longterm impact of practitioner research is rather disappointing because, we contend, it tends to lack practicality. We used theories of classroom ecology, goal systems and how people make decisions in complex situations, to conceptualise practicality from a teacher's perspective. By applying our theoretical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Methodical training of future physics teachers in pedagogical universities is carried out within a specially organized educational structure [6].…”
Section: Discussionmentioning
confidence: 99%
“…Methodical training of future physics teachers in pedagogical universities is carried out within a specially organized educational structure [6].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that innovative methods should be easily applicable for teachers. Demands regarding practicality (instrumentality, congruence, and low cost; Westbroek et al, 2020) should thus be considered. Accordingly, the unit should be open to contextual modifications.…”
Section: Design Principlesmentioning
confidence: 99%
“…As teachers commonly find it difficult to teach reading and writing strategies, the instruction must be made as easily integrable as possible, for them to maximize practicality. Practicality can be divided into three criteria, all related to classroom ecology and a teacher's goal system (Westbroek et al, 2020). A first criterion is instrumentality: are procedures available to show how the innovation should be implemented?…”
Section: Design Requirementsmentioning
confidence: 99%
“…If the teacher does not have good understanding of the reasoning behind a certain learning activity, there is a risk of conducting, or adapting, the learning activity in a non-constructive way: it may become much less meaningful. Previous research has shown that individuals rely on heuristics, when situations become complex, and time and information are limited (Westbroek et al, 2020). Thus, a teacher with a clear understanding of his own heuristics, and of the goals behind the material should be the goal.…”
Section: Recommendations For Redesignmentioning
confidence: 99%